Development of the Japanese version of the perceived time poverty scale - Takeshi Miura; Koji Hara; Azusa Arimoto; Masato Kaneko; Sayuri Shiraishi; Shingo Matsumura; Shuichi Ito; Kentaro Kurasawa; Yohei Matsuzaki; Makoto Kuroki (PLoS ONE, 2025)
Background Employed households experience time poverty, which refers to feeling overwhelmed because of the struggle to balance work and life. Time poverty is subjectively perceived as a lack of personal free time. In Japan, long working hours and societal expectations regarding the division of work and family roles may influence the perception of time poverty. This issue is of significant concern, as it can impact individuals’ rest time and work productivity. However, there is currently no standardized measurement method to assess time poverty appropriately in the Japanese context. The lack of such a method challenges establishing a foundation for developing effective support strategies. Given this background, this study aimed to quantify time poverty among employed households by developing a Japanese version of the Perceived Time Poverty Scale and examining its reliability and validity. Methods In developing the Japanese version of the Perceived Time Poverty Scale, cultural adaptations were made in addition to the standard translation and back-translation procedures. Through discussions with researchers and translation experts, terms with differing scopes of interpretation in the Japanese context were revised, and expressions were adjusted to reflect the intended concepts better. The data for this study were collected through Wave 2 of the longitudinal survey, the Hama Study, conducted over a five-year period from 2022 to 2027. This survey randomly selected 10,000 employed households residing in Yokohama, Japan. Participants completed the Japanese version of the Perceived Time Poverty Scale developed in this study, along with the well-being scale, the Kessler Screening Scale for Psychological Distress, and the Japanese Short-Form UCLA Loneliness Scale. Exploratory and confirmatory factor analyses were conducted to evaluate the scale structure. Internal consistency was assessed using Cronbach’s alpha and McDonald’s omega coefficients. Furthermore, correlations between the Japanese version of the Perceived Time Poverty Scale and the other scales were examined to evaluate the structural validity of the scale. Results Data from 1,979 respondents who participated in the Wave 2 online survey were analyzed. The scale demonstrated high reliability, with a Cronbach’s alpha coefficient 0.90 (95% CI: 0.89–0.91). Exploratory factor analysis confirmed a single-factor structure and confirmatory factor analysis supported this structure with fit indexes (CFI =  0.957, TLI =  0.929, RMSEA =  0.136, SRMR =  0.035). Perceived time poverty was negatively correlated with sleep time and leisure time, and positively correlated with childcare time. Furthermore, perceived time poverty showed significant correlations with well-being, psychological distress, social isolation, and job satisfaction, confirming the validity of the developed scale. Conclusion The Japanese version of the Perceived Time Poverty Scale is a reliable tool with a certain degree of validity for assessing time poverty in Japan. This scale enables individuals and households to recognize time poverty as a modern form of poverty. Furthermore, businesses and local governments can utilize it as an indicator in practical settings, such as improving work environments, implementing childcare support programs, and promoting community health. Future longitudinal studies are needed to further validate the scale, including addressing issues related to model fit.